Genome Medicine - Begum, Rabia; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Genome Medicine publishes outstanding research of broad interest in the application of genetics, genomics and multi-omics to understand, diagnose and treat disease. The Journal aims to bridge the basic science and clinical research communities in areas that include, but are not limited to, cancer genomics, immuno-oncology, immunogenomics, infectious disease, neurogenomics, cardiogenomics, clinical genomics, gene therapies, microbiome, systems medicine, precision medicine and clinical trials. The Journal welcomes submissions of original research, methodology, software and guideline articles as well as expert reviews and commentary across all areas of human health and disease. .
Keywords: Medical genetics; Bioinformatics; Bioinformatics; Public health; Cancer; Medical Genetics; Computational and Systems Biology; Bioinformatics; Public Health; Cancer Biology